Promoting Quality in BDD Scenarios Using Checklist: An Investigation from the Perspective of Novice Professionals - Goelzer, Natalya Marjana; Marczak, Sabrina (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
Providing high quality from the earliest stages is crucial to the success of software products. Checklists are effective tools for this purpose, as they make verification more consistent and repeatable due to their simple and effective structure. This study investigates the effectiveness of checklists as an inspection tool to improve novice practitioners’ understanding of scenario quality in Behavior Driven Development (BDD). Using Action Research, this study evaluated the impact of checklists in an IT Training Program which is developed in collaboration between a multinational company and the Pontifical Catholic University of Rio Grande do Sul. Data were collected through questionnaires. Results indicate that the use of checklist improves novices’ perception of the quality of scenarios, optimizing evaluation and providing greater clarity about the scenarios’ elements, promoting the reduction of questions asked and ambiguities in the writing. In addition, the adopted checklist improved the ability to evaluate the quality of BDD scenarios, making it easier to detect misunderstandings and identify information gaps. The checklist also helped to organize the evaluation process, increasing the ability of the reviewers to focus on details and allowing for a more effective and comprehensive analysis. In conclusion, the use of the checklist improved technical and collaborative skills, resulting in a higher quality development process.